Plant inhabiting mites (Acari) from the Cerrado biome of Mato Grosso State, Brazil - Demite, Peterson R.; Feres, Reinaldo J. F.; Lofego, Antonio C.; Oliveira, Anibal R. (Zootaxa, 2009)
This study reports on the mites associated with plants in two Cerrado formations: Cerradão and Riparian Forest, located in Itiquira, in the southern region of Mato Grosso State, Brazil. A total of 67 mite species was collected, belonging to 20 families in the suborders Gamasida, Actinedida, Acaridida and Oribatida. Phytoseiidae (13 species) and Tarsonemidae (11 species) were the families with the greatest richness. Iphiseiodes zuluagai (Denmark & Muma) (Phytoseiidae), Lamellobates (Lamellobates) sp. (Oribatida, Austrachipteriidae) and Agistemus sp. (Prostigmata, Stigmaeidae) were the most frequent species, collected on eleven, ten and nine plant species, respectively. Among the plants found during the fieldwork, the plant species Bauhinia longifolia (Bong.) Steud. (Caesalpinaceae), collected in the Riparian Forest formation, contained the highest species richness (28 species). The specific identification of approximately 70% of the taxa collected was not possible. For these reasons, surveys of mites in natural areas that include estimates of the ratio of undescribed species are important, because they provide a panorama of the great diversity of unknown mite fauna in these environments.